KOMPETENSI KEPEMIMPINAN DALAM MENINGKATKAN KREATIVITAS PEGAWAI MELALUI PENGEMBANGAN SDM DI SANGGAR SENI DAN BUDAYA KOTA PALANGKA RAYA - Tris Sofia Wartina; Roby Sambung; Vivy Kristinae; Achmad Syamsudin (LPSDI Bina Patria, 2022)
Research in the field of management aims to analyze the influence of Leadership Competence on Employee Creativity, analyze the influence of the Role of HRM on Employee Creativity and at the same time analyze employee creativity at an art studio in the city of Palangka Raya. The employee in question is an employee who works or manages parts that have been given responsibility by the Leader of the studio community. The sample in this study were 47 respondents. This study uses a quantitative approach and data collection by survey method. Data were collected using questionnaires and data analysis techniques using the Partial Least Square (PLS) structural model (SEM) assisted by the Smarth PLS program. The results of the study prove: 1) Leadership Competence has a significant effect on the Role of Human Resource Management, meaning that the better the leadership competence of the studio owner, the better is HR Management, which in this case is the person in charge of managing and seeing the potential of each individual. 2) HR management has a significant effect on employee creativity, meaning that the better the way of HR management, the creativity of employees or employees will also be more creative. 3) Leadership Competence has a significant effect on Employee Creativity, meaning that the better the Leadership Competence, the more creative the employees or employees will be. The implications of the results of the important role of HRM in increasing employee creativity. These results can be used as a reference in further research